Look closer - Ellis, David, 1967- (G. P. Putnam's Sons, 2023)
Simon and Vicky couldn't seem more normal: a wealthy Chicago couple, he a respected law professor, she an advocate for domestic violence victims. A stable, if unexciting marriage. But one thing's for sure ... absolutely nothing is what it seems. The pair are far from normal, and one of them just may be a killer. When the body of a beautiful socialite is found hanging in a mansion in a nearby suburb, Simon and Vicky's secrets begin to unravel. A secret whirlwind affair. A twenty-million-dollar trust fund about to come due. A decades-long grudge and obsession with revenge. These are just a few of the lies that make up the complex web...and they will have devastating consequences. And while both Vicky and Simon are liars, just who exactly is conning who?